Factors Influencing the Level of Intermediation of Rural Banks in Indonesia 2008:1 – 2010:8 - Jamil, Azimah; Kamio, Kamio; Supadi, Supadi (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This research entitled